KONSTRUKSI MAKNA BISINDO SEBAGAI BUDAYA TULI BAGI ANGGOTA GERKATIN - Gilang Gumelar; Hanny Hafiar; Priyo Subekti (Universitas Negeri Yogyakarta, 2018)
This research try to investigate the using of language by deaf. The theory used in thisresearch is the theory of Phenomenology Schutz. This research used constructivismparadigm with Phenomenology as the kind of research. Data collection techniques thatused are in-depth interviews, participatory observation, and the study of librarianship,the collecting techniques of key informants by snowball sampling. While the dataanalysis techniques using three stages, the first is reduction, the second is rendering,and the third is the withdrawal of the conclusion. Validity of data uses triangulationtechniques sources and triangulation techniques. The results of this research showthat the meaning of Bisindo as Deaf Culture for the informants who are the memberof DPC Gerkatin Jawa Barat, is categorized as affirmative meaning. The meaning of theaffirmative that is owned by the informants is when the informants consider that Bisindoas Deaf Culture, is an interest and pride. The study also found motifs belonging to theinformants in lifting the existence of Bisindo as Deaf Culture, not only the cause-motifbut also the purpose-motif. The informant’s experience, include the early experience inhow they get interest to Bisindo, the experience of using Bisindo, and the experienceto raise the existence of Bisindo as Deaf Culture that finally those communicationexperiences affect the way informants in conducting follow-up. Penelitian ini mengkaji tentang bahasa yang digunakan kaum tuli. Teori yang digunakan dalam penelitian ini adalah teori fenomenologi Schutz. Penelitian ini menggunakan paradigma konstruktivisme dengan jenis penelitian fenomenologi. Teknik pengumpulan data yang digunakan antara lain wawancara mendalam, observasi partisipatif, dan studi kepustakaan, dengan teknik pengumpulan key informant dengan cara snowball sampling. Sedangkan teknik analisis data menggunakan tiga tahap, yaitu reduksi, penyajian, serta penarikan kesimpulan. Teknik validitas data menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian ini menunjukan bahwa makna Bisindo sebagai Budaya Tuli bagi para informan yang merupakan anggota Gerkatin DPC Jawa Barat dikategorikan sebagai makna afirmatif. Makna-makna afirmatif yang dimiliki para informan adalah ketika informan menganggap Bisindo sebagai Budaya Tuli adalah sebuah kepentingan dan kebanggaan. Penelitian ini juga menemukan motif-motif yang dimiliki informan dalam mengangkat eksistensi Bisindo sebagai Budaya Tuli, baik itu motif sebab atau motif tujuan. Adapun pengalaman yang dimiliki informan, meliputi pengalaman awal ketertarikan pada Bisindo, pengalaman menggunakan Bisindo, dan pengalaman mengangkat eksistensi Bisindo sebagai Budaya Tuli yang akhirnya pengalaman komunikasi tersebut mempengaruhi cara informan dalam melakukan tindak lanjut